2005
DOI: 10.1002/tea.20096
|View full text |Cite
|
Sign up to set email alerts
|

“It isn't no slang that can be said about this stuff”: Language, identity, and appropriating science discourse

Abstract: This investigation explores how underrepresented urban students made sense of their first experience with high school science. The study sought to identify how students' assimilation into the science classroom reflected their interpretation of science itself in relation to their academic identities. The primary objectives were to examine students' responses to the epistemic, behavioral, and discursive norms of the science classroom. At the completion of the academic year, 29 students were interviewed regarding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
101
0
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(105 citation statements)
references
References 31 publications
1
101
0
3
Order By: Relevance
“…Studies indicate how the symbolic relationships between students' language and language valued in the classroom were often in conflict for minority students (Brown, 2004(Brown, , 2006Fordham & Ogbu, 1986;Malcolm, 1989). This study highlighted how the teacher's careful use of classroom language provided students with opportunities to appropriate the language of science in a variety of forms.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Studies indicate how the symbolic relationships between students' language and language valued in the classroom were often in conflict for minority students (Brown, 2004(Brown, , 2006Fordham & Ogbu, 1986;Malcolm, 1989). This study highlighted how the teacher's careful use of classroom language provided students with opportunities to appropriate the language of science in a variety of forms.…”
Section: Discussionmentioning
confidence: 90%
“…This use of everyday and scientific forms of language becomes pertinent when considering how students' experience with scientific language has served as a gatekeeper to student learning (Brown, 2004(Brown, , 2006Varelas et al, 2002). Research has demonstrated that perhaps the most contentious aspect of minority children's experiences in classrooms involves the conflicting features of their communicative style with those valued by the teacher and classroom (Gee, 1999;Malcolm, 1989;Williams, 1991).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Thus, as ironic as it might seem, it is by exposing the underprivileged to the discourses of the dominant cultural capital that social mobility can be made possible (Brown, 2006). Curriculum, paradoxically, becomes a factor that both helps individuals conform to the existing social structures and emancipate from them, and it is through this clash between freedom and conformance that curriculum/ schooling are shaping the agentive roles of learners.…”
Section: The Covert Interests Behind Curriculum Constructionmentioning
confidence: 99%
“…This perspective tended to emphasize science learning as mainly the challenge of existing prior knowledge and the acquisition of conceptual knowledge (assimilation of new ideas into an existing conceptual network or restructuring the conceptual network to accommodate discrepant ideas) and downplayed cultural differences in learners and the influence of different cultural contexts on learning. However, there has been a growing awareness of differences amongst learners' identities, values, and communication resources for learning that affect their interest and progress in the subject (Allen & Crawley, 1998;Brown, 2006;Kawagley, Norris-Tull, & Norris-Tull, 1998;Sutherland, 2002). Aikenhead (2003: 53) suggested that even many mainstream students view science as a "foreign culture that does not engage their self-identities" and lacking cultural relevance and that students are likely to respond more favorably to authentic inquiries that connect to their cultures, lives, beliefs, and values.…”
Section: Closing Remarksmentioning
confidence: 99%